2001
DOI: 10.1002/jcb.1072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1?,25-(OH)2D3 on rat growth zone chondrocytes are mediated via cyclooxygenase-1 and phospholipase A2

Abstract: Abstract1a,25-(OH) 2 D 3 mediates its effects on growth zone chondrocytes via rapid membrane-associated events as well as through traditional nuclear receptor mechanisms. The membrane-associated signaling pathways include rapid production of diacylglycerol and activation of protein kinase C (PKC), as well as activation of phospholipase A 2 (PLA 2 ), increased production of arachidonic acid, and increased production of prostaglandins. This study examined the roles of PLA 2 and cyclooxygenase (Cox) in the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
2
18
0
2
Order By: Relevance
“…Taken together with previously published studies [10], the results suggest the following pathway (Fig. 8): 1␣,25(OH) 2 D 3 binds the Pdia3-Cav-1 membrane receptor complex in caveolae, triggering binding of PLAA to Pdia3.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Taken together with previously published studies [10], the results suggest the following pathway (Fig. 8): 1␣,25(OH) 2 D 3 binds the Pdia3-Cav-1 membrane receptor complex in caveolae, triggering binding of PLAA to Pdia3.…”
Section: Discussionsupporting
confidence: 76%
“…PLA 2 action generates arachidonic acid (AA) and lysophospholipid (LPL) [7]. AA can either increase PKC␣ activity directly [9], or it is processed further to PGE 2 , which acts via its EP1 receptor to increase cyclic AMP [10]. Phosphatidylinositol-specific PLC␤ is activated via G␣q and lysophospholipid, generating diacylglycerol (DAG) and inositol 1,4,5-trisphosphate (IP3) [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Our current study provides the first evidence from immunohistochemistry that shockwave therapy can induce articular cartilages expression of Pdia-3, the critical transcription factor responsible for the matrix formation of chondrocyte. Recent studies reported that 1α,25(OH)2D3 rapidly stimulated membrane signaling via Pdia-3 dependent activation in growth zone chondrocytes and promotes the production of matrix protein [11,13,20,22,42,43]. The present study showed the decrease of cartilage matrix loss and increased aggrecan and collagen II expression in shockwave group.…”
Section: Discussionsupporting
confidence: 62%
“…1α,25-Dihydroxyvitamin D3 (1α,25(OH)2D3) is essential in calcium homeostasis to regulation of endochondral ossification [11]. In vitamin D deficiency, bone matrix synthesis and cartilage growth are inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, inhibition of arachidonic acid metabolism with the general cyclooxygenase inhibitor indomethacin causes growth zone cells and resting zone cells to respond to 1␣,25(OH) 2 D 3 and 24R,25(OH) 2 D 3 in a manner like their response to exogenous arachidonic acid. Inhibition of inducible cyclooxygenase 2 does not alter that response, whereas inhibition of constitutive cyclooxygenase 1 reduces the arachidonic acid-like effect [22]. This observation shows that PLA 2 is rate limiting because it changes substrate concencentration for the consistutive form of the enzyme, and it shows that metabolites of arachidonic acid are also involved in the mechanism.…”
Section: Pivotal Role Of Phospholipase Amentioning
confidence: 93%